Dying to be men psychosocial, environmental, and biobehavioral directions in promoting the health of men and boys - Courtenay, Will H. (Routledge series on counseling and psychotherapy with boys and men ;, 2011)
"Men have specific gender-related influences that can affect their health and psychological well-being, and it is thus necessary for mental health practitioners to be knowledgeable in effective interventions for working with them. The purpose of this book is to provide a thorough foundation for understanding men health and risks and the differences between men. It will discuss effective, evidence-based strategies for practitioners to improve the health and well being of boys and men by drawing from a wealth of literature and research in a diverse array of disciplines, as well as from the authors original research designed specifically to examine gender and men's health"--Provided by publisher.